UNIVERSITAS AL-AZHAR SEJAK ABAD KE-20 - Muhammad Idris (Studi Multidisipliner: Jurnal Kajian Keislaman, 2018)
Al-Azhar in its development, not only as a place to study religion or shelter for the poor, even al-Azhar is also a unifying place for the people in the struggle to free Egypt from colonialism. The specialty of al-Azhar is not only skilled in producing quality scholars, but it also builds world civilization in two ways, namely the personality possessed by al-Azhar itself, and through its graduates who bring change to the world community. Al-Azhar not only becomes history, but witnesses and carves history in the wonders of the world of education and civilization. And the existence of al-Azhar is clear evidence that Islam is a religion that cares about education, health, arts, and other general sciences.